Effects of foliar iron amino acids fertilizer on iron content and nutrition quality of rice grain - LÜ Qian; WU Liang-huan; XU Jian-long; SHOU Hui-xia; YANG Xiao-e (浙江大学学报. 农业与生命科学版, 2010)
A field experiment was carried out to investigate the effects of new foliar iron amino acids fertilizer [Fe(Ⅱ)-AA] on iron content and nutrition quality in polished rice of different varieties under split plot design. Eight varieties of high iron content rice were applied. The results demonstrated that foliar Fe (Ⅱ)-AA could promote significantly iron content in polished rice of different varieties. After Fe (Ⅱ)-AA spraying, the total average iron content in polished rice of eight varieties was 3.99 mg·kg-1, increased significantly by 19.46% compared with control. The highest polished rice iron content was 4.97 mg·kg-1, increased significantly by 34.62% compared with control, and observed in rice mutant “Nipponbare”. In addition, foliar Fe (Ⅱ)-AA could also increase significantly protein content and essential amino acids including lysine in polished rice. The total amino acid contents were simultaneously increased. In conclusion, foliar Fe (Ⅱ)-amino acids provided an effective and economic strategy to enrich iron content and nutrition quality in rice grain.